Development of biology e-modules on environmental change integrated with wahdatul ulum - Nasution, Elyda Khairani; Anas, Nirwana (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to develop teaching materials in the form of biology E-Modules on environmental change materials integrated with Wahdatul Ulum in class X SMA/MA, which are valid, practical, and effective with the Four-D model, which includes the stages of defining, designing, developing, and disseminating. The research was conducted on class X-A students at MAN 2 Model Medan. The types of data used are quantitative and qualitative. Quantitative data were obtained through validation test sheets, practicality test sheets, and effectiveness test sheets. Meanwhile, qualitative data was obtained through suggestions and criticisms from validators and educators. Data collection instruments were carried out by observation, validity test, practicality test, and effectiveness test. The results of this study illustrate that (1) A score of 90,38% (Very Valid) was obtained on material testing, 97% (Very Valid) on media validation testing, and 96,66% (Very Valid) on religious validation testing. (2) A score of 80% (Practical) was obtained in the practicality test, which included testing the educator's response, and 78% (Practical) in testing the students' response. (3) A value of 0,53 (Moderate) or (Quite Effective) was obtained on the student learning outcomes test by evaluating the pre-test and post-test, referring to the N-gain scale.